1998
DOI: 10.1074/jbc.273.20.12352
|View full text |Cite
|
Sign up to set email alerts
|

Induced Activation of the Toxoplasma gondiiNucleoside Triphosphate Hydrolase Leads to Depletion of Host Cell ATP Levels and Rapid Exit of Intracellular Parasites from Infected Cells

Abstract: The nucleoside triphosphate hydrolase of Toxoplasma gondii is a potent apyrase. The protein is synthesized in large amounts and transported through the secretory pathway of the parasite and into the vacuolar space in an oxidized and thereby enzymatically inactive form. Complete activation of the purified enzyme is known to require dithiols (e.g. DTT); subcellular fractionation demonstrates that little if any (<5%) of the enzyme in the vacuolar space is active in the absence of DTT. Both native and epitope-tagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 22 publications
4
52
0
1
Order By: Relevance
“…NTPase isoforms are apyrases, which were demonstrated to function in intracellular replication of the parasite based on antisense interruption of expression (73). Also, the full scale activation of NTPase with dithiols may contribute to parasite exit from the host cell (74). It is likely that several of the novel secretory products identified herein are also derived from the DGs.…”
Section: Discussionmentioning
confidence: 99%
“…NTPase isoforms are apyrases, which were demonstrated to function in intracellular replication of the parasite based on antisense interruption of expression (73). Also, the full scale activation of NTPase with dithiols may contribute to parasite exit from the host cell (74). It is likely that several of the novel secretory products identified herein are also derived from the DGs.…”
Section: Discussionmentioning
confidence: 99%
“…Exit of parasites in response to thiol compounds is Ca 2ϩ dependent, suggesting that ATP depletion releases Ca 2ϩ stores that are controlled by ATP (141). These data all suggest that the activation of a secreted NTPDase must be tightly regulated by the parasite (131). Recently, it has been shown that the reducing agent glutaredoxin (GRX) is secreted by the parasite as replication increases.…”
Section: Purine Salvage and The Apicomplexan Parasitesmentioning
confidence: 99%
“…However, since parasitic infections generate host nitric oxide and other free radicals, which results in oxidative and nitrative stress (165), it may be that T. gondii itself is responsible for the reduction and therefore activation of NTPDase 3. Upon activation of the enzyme by exogenous thiols, the level of ATP in the host cell is rapidly depleted, and the parasites exit the host cell within a minute of thiol treatment (131). Exit of parasites in response to thiol compounds is Ca 2ϩ dependent, suggesting that ATP depletion releases Ca 2ϩ stores that are controlled by ATP (141).…”
Section: Purine Salvage and The Apicomplexan Parasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the treatment of Toxoplasma-infected cells with the strong reducing agent DTT 1 results in the rapid egress of the parasites (11). The mechanism of action of DTT is not clear but may involve the artificial activation of parasitic nucleoside triphosphate hydrolases (12).…”
mentioning
confidence: 99%